Strain energy in hybrid nanowire structures with axially varying eigenstrain. (1st November 2022) - Kolesnikova, Anna L.; Gutkin, Mikhail Yu.; Romanov, Alexey E.; Bougrov, Vladislav E.
Abstract: The strain energy states of nanowires (NWs) with axial variation in either chemical composition or temperature are considered. Such nonuniformities from the mechanical point of view are described as axially varying eigenstrain in the material interior. The nanodisk/nanowire (ND/NW) hybrid structures comprising of a single or a pair of interacting nonuniformities which can be also treated as dilatational inclusions (DIs) formed in a NW, are analysed. The cases of sharp (abrupt) and smooth (diffuse) variations of eigenstrain are compared. It is shown that the energy conditions dictate an increase in the length of the transition region between the NW parts of constant eigenstrain.